2019
DOI: 10.3389/fpsyg.2019.02632
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Social Resources at Work: Reciprocal Relations Between Crafting for Social Job Resources, Social Support at Work and Psychological Capital

Abstract: The availability and development of social and personal resources are substantial components of a positive work experience. This study aims to inquire the reciprocal relations between the personal resource of psychological capital (PsyCap; hope, self-efficacy, resilience, and optimism) and the social job resource of social support, as proposed in the job demands-resources theory. There, job crafting is defined as a catalysator to the interplay of social support and PsyCap and is therefore added to this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 64 publications
7
30
0
Order By: Relevance
“…Regarding the socio‐environmental conditions that may foster job crafting, our results showed that perceived colleague support was associated with more seeking resources and more reducing demands but did not relate to seeking challenges, thus providing partial support for Hypothesis 3. Our results thus corroborate prior research (Audenaert et al., 2020; Kerksieck et al., 2019) by showing that when they have social resources (i.e., colleague support), employees are likely to seek more resources. Moreover, our study shows that colleague support may act as a safety net allowing employees to reduce the hindering demands of their job without fearing negative interpersonal consequences for their behaviours (Plomp, Tims, Khapova, Jansen, & Bakker, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the socio‐environmental conditions that may foster job crafting, our results showed that perceived colleague support was associated with more seeking resources and more reducing demands but did not relate to seeking challenges, thus providing partial support for Hypothesis 3. Our results thus corroborate prior research (Audenaert et al., 2020; Kerksieck et al., 2019) by showing that when they have social resources (i.e., colleague support), employees are likely to seek more resources. Moreover, our study shows that colleague support may act as a safety net allowing employees to reduce the hindering demands of their job without fearing negative interpersonal consequences for their behaviours (Plomp, Tims, Khapova, Jansen, & Bakker, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies have further explored this idea that employees' job crafting may depend on the social support provided by their coworkers. For instance, researchers found social support to positively predict employees' crafting for social job resources 3 months later (Kerksieck, Bauer, & Brauchli, 2019). Yet, this study only explored one facet of the seeking resources strategy (i.e., social job resources), thus omitting employees' seeking structural job resources and challenging demands, and their reducing hindering job demands.…”
Section: Introductionmentioning
confidence: 99%
“…No study, to our knowledge, has directly examined the relationship between job crafting and work volition, though the literature does contain results on job crafting and psychological capital, an antecedent of work volition (Cheung et al, 2020). According to these results, job crafting positively influenced the development of employees' psychological capital (Kerksieck et al, 2019) and predicted psychological capital over time (Vogt et al, 2016).…”
Section: Results Of Job Crafting Research and The Pwt Model Of Decent Workmentioning
confidence: 99%
“…Third, job crafting is mediated by career adaptability (e.g., Federici et al, 2019 ), as is seeking decent work. Fourth, job crafting indirectly enhances work volition ( Vogt et al, 2016 ; Kerksieck et al, 2019 ; Cheung et al, 2020 ), the second mediator involved in seeking decent work. Thus, job crafting seems to help workers achieve job characteristics dealing with decent work, specifically those related to self-determination.…”
Section: Discussion: Can Job Crafting Shape Decent Work For Vulnerable Workers?mentioning
confidence: 99%
“…At the same time, on the one hand, stock liquidity may promote mergers and acquisitions between enterprises, making managers face the pressure of mergers and acquisitions. Social psychology theory believes that the environmental atmosphere will affect people's motivations, thereby affecting people's behavioral decisions (Kerksieck et al, 2019;Wu et al, 2020). The psychological expectation of mergers and acquisitions (M&A) pressure will aggravate management's short-sighted behavior, thereby reducing corporate innovation (Nguyen and Nguyen, 2020;Garcia-Sanchez, 2021).…”
Section: Introductionmentioning
confidence: 99%